Exploring sub-optimal response to tumour necrosis factor inhibitors in axial spondyloarthritis. Issue 1 (4th May 2019) - Yahya, Fariz; Gaffney, Karl; Sengupta, Raj
Abstract: Objectives: The aim was to define sub-optimal response to TNF inhibitors (TNFi), compare long-term drug survival rates and identify predictors of sub-optimal response in axial spondyloarthritis (axSpA) patients in a UK cohort. Methods: All axSpA patients attending two centres who commenced TNFi between 2002 and 2016 were included. Routinely recorded patient data were reviewed retrospectively. Patients with paired BASDAI at baseline, 3 and/or 6 months were included for analysis. Sub-optimal response was defined as achieving a ≥ 2-point reduction in BASDAI but not BASDAI50, post-treatment BASDAI remaining at ≥4, and in the opinion of the treating physician these patients demonstrated a meaningful clinical response. Results: Four hundred and ninety-nine patients were included: 82 (16.4%) patients were classified as having a sub-optimal response; 64 (78%) males, 78 (95.1%) AS and 55/67 (82.1%) HLA-B27 positive. Results are reported as the mean (s .d .). Time to diagnosis was 10 (8.6) years, age at diagnosis was 37 (11.7) years, and age at initiating index TNFi was 48 (11.1) years. Individual index TNFi were Humira (adalimumab, n = 41, 50%), Enbrel (etanercept, n = 27, 32.9%), Remicade (infliximab, n = 5, 6.1%), Simponi (golimumab, n = 3, 3.7%) and Cimzia (certolizumab pegol, n = 6, 7.3%). The rate of attrition was greater among sub-optimal responders at 2 and 5 years ( P < 0.05), but not at 10 years ( P = 0.06), compared with responders. Older age at initiation of TNFi was a predictor of sub-optimal response (odds ratio 1.04, 95% CI 1.01, 1.09, P < 0.05). Conclusion: A significant proportion of patients continued TNFi despite demonstrated sub-optimal response. Further research needs to be undertaken in order to understand this group.